CLINICAL AND ECONOMIC EVALUATION OF ERIBULIN EFFECTIVENESS IN SOFT TISSUE SARCOMA: RESULTS OF META-ANALYSIS - P. V. Мazin; I. V. Sheshunov; N. K. Mazina; E. M. Markova (IRBIS LLC, 2017)
Innovative drugs eribulin and trabectedin are effective in the treatment of soft tissue sarcomas (STS) - rare, but severe malignancies.Aim of the study. To perform the pharmacoeconomic evaluation of these two agents used with the second and subsequent lines of chemotherapy in common/metastatic STS, in theRussian Federation.Materials and Methods. Direct, indirect and meta-analytic comparisons were applied to the results of two multicenter, randomized phase III clinical studies, on effectiveness and safety of trabectedin and eribulin as compared with dacarbazine for the treatment of severe anthracyclines-resistant lipoand leiomyosarcoms. The 12-month survival rate and the occurrence of adverse events were the endpoint parameters in this study. The impact on the budget and the "cost-effectiveness" index were also analyzed.Results. The relative number of patients, who survived for 12 months and continued their treatment with the given drug, was 53% in the eribulin group, and 18% in the trabectedin group. The total number of recorded adverse events was not significantly different between eribulin and dacarbazine. The incidence of adverse events (including haematological) in the trabectedin group was significantly higher than that in the dacarbazine group (lg 95% CI> 1.0). The cost values of different treatment doses of eribulin got into a zone of 1-2 willingness to pay threshold (WPT). The cost of trabectedin treatment was higher than that of eribulin, and even at mid-optimal doses (1.5 mg/m2 ) exceeded 2xWPT. The cost estimating relationship (CER) was 0.69 for trabectedin, and 0.15 for eribulin.Conclusion. In the Health Care system ofRussia, eribulin has a more favorable pharmaco-economic profile than trabectedin. Since STS is viewed as an orphan disease, both drugs are considered important and promising for the Russian oncological services.